2010
DOI: 10.3109/01902140903061787
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the expression of inflammatory parameters as a result of oxidative stress produced by moderate zinc deficiency in rat lung

Abstract: Suboptimal intake of dietary zinc (Zn) is one of the most common nutritional problems worldwide. Previously, the authors have shown that zinc deficiency (ZD) produces oxidative and nitrosative stress in lung of male rats. The goal of this study is to test the effect of moderate ZD on insulin-like growth factor (IGF)-1, IGF-binding protein (IGFBP)-5, NADH oxidase (NOX)-2, tumor necrosis factor alpha (TNFalpha), as well as the effect of restoring zinc during the refeeding period. Adult male rats were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 59 publications
4
21
0
Order By: Relevance
“…We have previously demonstrated an increase in the gene transcription of many inflammatory cytokines such as TNF-a during Zn deficiency. In agreement with this, an important infiltration of inflammatory cells, principally, neutrophils (data not shown) was observed in our experimental model (6) . Besides, some authors have shown the relationship between TNF-a and other fibrogenic molecules with a fibrotic sequel, in particular TGF-b1.…”
Section: Discussionsupporting
confidence: 90%
“…We have previously demonstrated an increase in the gene transcription of many inflammatory cytokines such as TNF-a during Zn deficiency. In agreement with this, an important infiltration of inflammatory cells, principally, neutrophils (data not shown) was observed in our experimental model (6) . Besides, some authors have shown the relationship between TNF-a and other fibrogenic molecules with a fibrotic sequel, in particular TGF-b1.…”
Section: Discussionsupporting
confidence: 90%
“…Zinc has an activating effect on the antioxidant system (8). Several researchers reported that zinc defi ciency in the organism caused lipid peroxidation (19,20,21). The results we obtained in the Group 3 in our study are consistent with the studies highlighting the antioxidant character of zinc.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, Zn deficiency in rats resulted in a significant increase in proinflammatory TNFα and VcAM-1 expression and lung tissue remodeling, being partially reversed by Zn supplementation (105). Zn deficiency also resulted in a significant alteration of lung epithelial cell barrier function through up-regulation of TNFα, IFNγ, and FasR signaling and cellular apoptosis in vitro (106).…”
Section: Zinc and Lung Inflammationmentioning
confidence: 99%